Occurrence and significance of cell inclusions in Rubiaceae - D.A. Patil2, Patil C.R.1 and (Current Botany, 2011)
The present communication embodies the results of foliar anatomical studies in 40 species of the family Rubiaceae. Particularly, diverse crystal forms such as raphides, rosette crystals, druses, crystal-sand and granular matter have been recorded from various foliar tissues. All these types are totally absent in three species. In others, they either occur singly or in different combinations. The authors also discussed them taxonomically. Evidence has been also borrowed from past literature, besides author’s own work. The present authors, however, cautioned their use in taxonomy and suggested their use only after critical investigations in the alliance.